2012
DOI: 10.1002/wcc.199
|View full text |Cite
|
Sign up to set email alerts
|

Local people's accounts of climate change: to what extent are they influenced by the media?

Abstract: Researchers using local and indigenous people's accounts of climate change in their scientific work often face scepticism regarding the value of such information. The critics' argument is that since local and indigenous people are often exposed to the global discourse on climate change, their observations and information may in fact be reproductions of science popularized through communication media. There are instances in which local people's accounts of climate change and impacts thereof may be influenced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 55 publications
(103 reference statements)
4
37
0
2
Order By: Relevance
“…Their observations rely on their personal experience and are more detailed than science and media discourse on global climate change (Marin and Berkes 2013). People's general observations of change were consistent with scientific observations (Perez et al 2010, Marengo et al 2011, and went beyond merely temperature increases to include unpredictability of rainfall, increase of extreme events, and incidence of pests.…”
Section: Discussionmentioning
confidence: 99%
“…Their observations rely on their personal experience and are more detailed than science and media discourse on global climate change (Marin and Berkes 2013). People's general observations of change were consistent with scientific observations (Perez et al 2010, Marengo et al 2011, and went beyond merely temperature increases to include unpredictability of rainfall, increase of extreme events, and incidence of pests.…”
Section: Discussionmentioning
confidence: 99%
“…While our understanding of climate change benefits from scientific gathering of world data and the construction of generic models, on-the-ground research is the micro-foundation of global environmental change research because this is how it is experienced and lived (and adapted to) by both ecosystems and human populations. As argued by Marin and Berkes (2013), climate change media discourse can influence local people's perceptions, but these tend to be only superficial. Local people experience their environment differentially and can discern local processes beyond these superficial narratives.…”
Section: Unpredictable Seasonsmentioning
confidence: 96%
“…Nevertheless, in a recent study by Marin and Berkes (2013), media accounts of climate change were reported to be largely irrelevant to local communities, as a result of the contrasting epistemological positions between the media and the communities. Accordingly, they argue that climate change knowledge of local nonscientific communities is not influenced by media frames of climate change alone but more readily shaped by a range of information sources and the interplay between the sources 3 (Marin and Berkes 2013).…”
Section: Introductionmentioning
confidence: 92%
“…The mass media's role in providing informal nonscientific climate change education has received considerable academic attention (Bell 1994b;Wilson 2000a,b;Carvalho and Burgess 2005;Boykoff 2007a,b;Boykoff and Boykoff 2007;Ryghaug et al 2011;Marin and Berkes 2013). Media agenda setting theory (Atwater et al 1985;Zhu and Blood 1997) suggests that the salience of an issue can be raised through increased media attention (Sherry 2002).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation